Histochemically distinct compartments in the striatum of human, monkeys, and cat demonstrated by acetylthiocholinesterase staining. - Graybiel, A M (1978)
We here report observations on the distribution of acetylcholinesterase (acetylcholine hydrolase, EC 3.1.1.7) in the striatum of the adult human, the rhesus monkey, and the cat. By the histochemical staining methods of Geneser-Jensen and Blackstad and of Karnovsky and Roots, compartments of low cholinesterase activity were identified in parts of the striatum in all three species. In frontal sections, these enzyme-poor zones appeared as a variable number of weakly stained approximately 0.5-mm-wide zones embedded in a darkly stained background. The zones varied in cross-sectional shape from round to elongated and were sometimes branched. They were most prominent in the head of the caudate nucleus. Three-dimensional reconstructions of serial sections through the caudate nucleus in the human and cat suggest that over distances of at least several millimeters, the zones of low enzyme activity form nearly continuous labyrinths.